The importance of marketing innovation in new economy - Ilić, Dejan; Ostojić, Slavica; Damnjanović, Nemanja (The European Journal of Applied Economics, 2014)
The new economy is greatly determined by the globalization process, radical and frequent changes, as well as the growing importance of knowledge application through the successful implementation of innovation. These determinants directly affect the fact that sustainable competitive advantage primarily reaches organizations that have developed the ability to improve the level of efficiency and effectiveness with the constant development of the total innovation performance. In the new economy, organizations that have the ability to develop and adopt the invention in a short period of time and profitably apply it in all areas of business reach competitive advantage over the competition in time. The growing importance of innovation in function of achieving a sustainable competitive advantage determined a brand new concept and innovation classification. Nowadays, the term innovation means not only a significant improvement in process and product technology, but it refers more to the innovation process in the field of human resources, especially in marketing management. For the above mentioned reasons, the paper pays special attention to the marketing innovation analysis and the increasingly significant impact it has on the process of achieving sustainable competitive advantage.